Media environments and interfaces in distance learning. Ethnography of online lessons during the Coronavirus emergency - Dentico, Michele; Mariani, Enrico; Pelusi, Francesco (E|C, 2021)
The Coronavirus pandemic and the restrictive measures taken at an institutional level have stimulated extensive reflection and debate on the topic of “distance learning”. The increasing presence of virtual interfaces in everyday life implies, in fact, what can be defined as a "migration" of practices towards media environments. The present contribution illustrates the partial results of a research path that, begun during the first lockdown, intends to investigate the relational dynamics that occur within media environments and that, at the same time, contribute to shape them. The ethnographic technique of data collection allows, on the one hand, to highlight the role of the enunciative brands of the interface in delineating the media environment, and, on the other hand, to unimply how a certain “normative” discourse of teaching is always implicit and allows us to draw lines of continuity and discontinuity with the “in presence” modality.